Hukum Pidana Dan Tantangan Penegakan Keadilan Terhadap Kejahatan Berbasis Platform Media Sosial - Bambang Kusnadi; Ayu Septiani; Ninda Widia Sari (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2025)
This study systematically examines the challenges of criminal law in upholding justice for social media-based crimes. Social media has evolved into a digital public space that facilitates various forms of crime, from fraud and hate speech to online gender-based violence, to organized crime and digital radicalism. The rapid, anonymous, and transnational nature of these crimes poses serious challenges for criminal law, which still relies on conventional paradigms. This study uses a normative legal approach enriched by socio-legal and digital criminology perspectives. Data were obtained through a literature review of laws and regulations, academic literature, and policy studies related to social media crimes. Qualitative analysis was conducted by examining the suitability of legal norms, law enforcement practices, and the influence of social media dynamics on the criminal justice process. The results indicate that upholding justice for social media crimes faces normative, institutional, and technical challenges. Limited legal norms, gaps in the capacity of authorities, the complexity of digital evidence, and pressure from public opinion through the phenomenon of viral justice affect the objectivity and consistency of law enforcement. The virality of cases has been shown to have the potential to shift the orientation of justice from substance to symbolism. This study concludes that criminal law needs to be developed adaptively and integratively to respond to social media-based crimes. Policy reform, institutional capacity building, and a balance between due process and the demands of the digital public sphere are essential prerequisites for achieving fair and sustainable justice enforcement. This approach is expected to maintain the legitimacy of criminal law in a digital society that is constantly changing critically and sustainably.